Effects of Soy Isoflavones and Green Tea Extract on Simvastatin Pharmacokinetics and Influence of the SLCO1B1 521T > C Polymorphism - Zeng, Weiwei; Hu, Miao; Lee, Hon Kit; Wat, Elaine; Lau, Clara Bik San; Ho, Chung Shun; Wong, Chun Kwok; Tomlinson, Brian (Frontiers in Nutrition, 2022)
Objectives: Green tea and soy products are extensively consumed by many people and they may influence the activity of drug metabolizing enzymes and drug transporters to result in drug interactions. This study was performed to evaluate the effect of green tea and soy isoflavone extracts on the pharmacokinetics of simvastatin in healthy subjects and to clarify the role of polymorphisms in the SLCO1B1 drug transporter in this effect. Methods: This was an open-label, three-phase randomized crossover pharmacokinetic study. A single dose of simvastatin 20 mg was taken on three occasions (without herbs, with green tea, with soy isoflavones) by healthy male Chinese subjects. The green tea and soy isoflavone extracts were given at a dose containing EGCG 800 mg once daily or soy isoflavones about 80 mg once daily for 14 days before simvastatin dosing with at least 4-weeks washout period between phases. Results: All the 18 subjects completed the study. Intake of soy isoflavones was associated with reduced systemic exposure to simvastatin acid (geometric mean (% coefficient of variation) AUC0-24h from 16.1 (44.2) h‧µg/L to 12.1 (54.6) h‧µg/L, P<0.05) but not the lactone. Further analysis showed that the interaction between simvastatin and the soy isoflavones only occurred in subjects with the SLCO1B1 521TT genotype but not in those with the 521C variant allele. There was no overall effect of the green tea extract on simvastatin pharmacokinetics but the group with the SLCO1B1 521TT genotype showed reduced AUC values for simvastatin acid. Conclusions: This study showed repeated administration of soy isoflavones reduced the systemic bioavailability of simvastatin in healthy volunteers that was dependent on the SLCO1B1 genotype which may suggest it is mediated by activation of this liver uptake transporter.